A Knowledge on Non-Communicable Disease among Patient Visitors Attending to a Tertiary Level Hospital of Chitwan, Nepal - Dhakal, Bijaya; Shrestha, Laxmi; Paudel, Madhumaya (Journal of National Heart and Lung Society Nepal, 2024)
Background: Non communicable diseases are a major contributor to the burden of disease in developed countries and are increasing rapidly in developing countries. This is mainly due to demographic transitions and changing lifestyle of population associated with urbanization. The impact of NCDs is devastating in term of premature morbidity, mortality, and economic loss. This study aimed to ware to find out the knowledge on non-communicable disease among patient visitors attending tertiary level hospital.Methods: A descriptive Cross sectional study design was used where122 patient visitors aged 24-44 years were purposively selected and enrolled in the study. Data were collected using face to face Interview questionnaire. Obtained data was analyzed in SPSS version 27 for window using descriptive and inferential statistics.Results: The finding of the study revealed that 59.8% respondents were from 24-44 years where 80.9% of the respondents were female. All most all (92.6%) of respondents were married,96.7% of respondents were literate. Regarding heard about NCDs, all most all (99.2%) of respondent were heard. Regarding family history of NCDs, more than half (59.8%) of respondent had present. This study showed 87.7% had good knowledge where 3.3% has poor Knowledge on overall Non-Communicable Disease.Conclusion: This study concluded that majority of respondents have good knowledge on overall non communicable disease so further studied should focus on identifying practices whether they are implementing their knowledge on day-to-day life or not.